Screening the Activity of Epigallocatechin Gallate as a Colorectal Anticancer Agent: In Silico and ADMET/Pharmacokinetic Studies - Setiadi, Prismo Bagas; Alamsyah, Maura Shavira; Ningsih, Tria; Fajriyah, Qatrunada; Febriansah, Rifki (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Introduction - Colorectal cancer is one of the third ranked cancers in Indonesia and has a high level of malignancy. The bioactive compound Epigallocatechin Gallate (EGCG) is known to have antioxidant and cytotoxic activity, so it has the potential to be developed as an anticancer agent. Purpose - This study aims to determine the potential of EGCG compounds as anticancer in silico. Methodology/Approach - The in-silico tests used are molecular docking and ADMET/Pharmacokinetic profiles using biosig pkcsm.Finding - The results of the respective binding affinities formed from EGCG compounds with the target protein affinities of COX-2 and Caspace-3 are -9.2 and -5.4 which are better links between EGCG and Caspace. The Lipinski rule show that the epigallocatecin compound has strength to absorb is 47%. This indicates that EGCG has the potential as a candidate for colorectal anticancer drugs with poor absorption. Originality/Value/Implications – In Silico, many studies have been carried out, but it is still rare to combine molecular docking methods with pKCSM to determine the solubility properties of compounds. The prospect of this research can become a basic or key for developing ECGC compounds into preparations because they have low bioavailability and can be continued in in vitro and in vivo research.